ANALYSIS OF FACTORS AFFECTING INCOME OF EMPING MELINJO BUSINESS OF HOUSEHOLD SCALE - Nursamsi Nursamsi; Sasmita Siregar; Nurul Iqbal (JASc (Journal of Agribusiness Sciences), 2017)
This research was purposed to find out the income, influence of production factors such as venture capital, materials, and workers with income of emping melinjo’s household scale, to know appropriateness level of emping melinjo’s household scale business. The result showed that average income of emping melinjo business was Rp.613.968,75 / month. The statistical test of R-square value of 0.98% simultaneously, there was a close relationship between venture capital,  materials and workers with income of emping melinjo’s household scale 98% the rest was  influenced by other factors that were not studied, it was supported by the value of f-count 304,285> f-table 2.95 at 95% confidence level. The calculation of R / C Ratio obtained value of 1.97, this value meant that the business emping malinjo household scale was feasible to cultivateKeywords: Income, Household Scale, Emping Melinjo